Effect of Supercritical Incorporation of Cinnamaldehyde on Physical-Chemical Properties, Disintegration and Toxicity Studies of Pla/Lignin Nanocomposites - Constandil-Cordova, L; Rodriguez-Mercado, F; Romero-Figueroa, J; Yanez-Sanchez, M; Galotto-Lopez, M; Rojas-Sepulveda, A; Torres-Mediano, A; Cerro-Munoz, D; Villegas-Vallejos, C (Elsevier B.V., 2021)
Poly (lactic acid)/lignin nanocomposites (PLA/Lig-Np) containing cinnamaldehyde (Ci) were obtained by a combination of melt extrusion and supercritical impregnation process. In this work, Ci impregnation tests were carried out in a high-pressure cell at 40 °C for 3 h using 12 MPa and 1 MPa min−1 of depressurization rate, obtaining impregnation yields ranging from 5.7 to 10.8% w/w. Thermal, mechanical and colorimetric properties of the developed films were affected by the incorporation of lignin nanoparticles and the active compound, obtaining biodegradable plastic materials with a strong UV-light barrier property compared to PLA films. In addition, disintegrability tests under composting conditions confirmed the biodegradable character of nanocomposites developed. On day 23, a disintegration percentage greater than 90% was determined for all bionanocomposites. Finally, to establish the possible toxicity effect of the nanocomposites obtained, studies in vivo were performed in normal rats. Toxicity studies showed normal blood parameters after a single dose of nanocomposites. PLA/Ci/Lig-Np bionanocomposite films could be potentially applied to design biodegradable UV-light barrier materials for food packaging and biomedical applications. © 2020 Elsevier B.V.